Understanding the Interrelationship between Education, Income, and Obesity among Adults in Saudi Arabia - Hala H. Mosli; Hebah A. Kutbi; Ahmed H. Alhasan; Rana H. Mosli (Obesity Facts, 2020)
Objective: To examine the association of sociodemographic variables with the odds of being obese among adults in Saudi Arabia, and to examine whether or not the association between the educational level and the odds of being obese among adults in Saudi Arabia is modified by the income level. Methods: A total of 3,925 participants were recruited for this cross-sectional study. Sociodemographic and anthropometric data were collected using standardized procedures. Unadjusted and adjusted logistic regression models were examined, with a dichotomous obesity status variable as the outcome. Furthermore, an interaction term for income level with educational level was tested and appeared significant. Thus, additional regression models were run in order to examine the association between educational level and obesity status separately among the low- and higher-income groups. Results: Compared to participants with a college degree or higher, illiterate participants and those with an elementary education had higher odds of obesity (OR: 2.76, 95% CI: 1.81–4.22, and OR: 2.68, 95% CI: 1.89–3.82, respectively). However, participants with a low income had lower odds than participants who had a higher income (OR: 0.84, 95% CI: 0.70–0.99). Examining the association between educational level and obesity while stratifying by income revealed that a negative association between education and obesity exists among both income groups. However, the magnitude of the ORs was higher among participants with higher income, suggesting a stronger association between education and obesity among wealthier individuals. Conclusion: Individuals in the highest income bracket with lower levels of education may have greater odds of obesity. Targeting them in intervention programs is warranted.